ANALYSIS OF THE EFFECT OF FINANCIAL RATIO ON FINANCIAL DISTRESS CONDITIONS IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Normiati Normiati; Diah Amalia (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to analyze any indicators in financial ratios that affect financial distress conditions. The data used are data on manufacturing companies in the Indonesia Stock Exchange (IDX) in 2012-2017, which are as many as 80 samples. Dependent financial distress variables are measured using the Altman analysis model (Z-Score). Independent variables are measured using the financial ratios indicator. This study uses a non-probability sampling technique that is purposive sampling. The data used is panel data, using Eviews 9. The results of this study show that the liquidity ratio measured by the current ratio and the leverage ratio measured by the debt asset ratio affect the condition of financial distress. While the profitability ratio measured by return on assets and sales growth does not affect the financial ratio. This research contributes to investors who can use this model, by including the financial ratios indicator, to assess the financial health of the company before making investment-related decisions.